2018
DOI: 10.3390/ijms19051386
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides Extracted from Rhizoma Pleionis Have Antitumor Properties In Vitro and in an H22 Mouse Hepatoma Ascites Model In Vivo

Abstract: Malignant ascites is a highly severe and intractable complication of advanced or recurrent malignant tumors that is often immunotherapy-resistant. Rhizoma Pleionis is widely used in traditional medicine as an antimicrobial and anticancer agent, but its effectiveness in treating malignant ascites is unclear. In the current study, we investigated the effect of polysaccharides isolated from Rhizoma Pleionis (PRP) on murine hepatocarcinoma H22 cells in an ascites model. We have found that the main components of PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The authors revealed that on the tenth day after tumor cell inoculation, the mouse abdominal perimeter and weight in the PRP treatment group were significantly smaller than those in the control group. Collectively, these results demonstrated that PRP has significant antitumour properties in the H22 tumor model [218]. Other studies in xenograft analysis showed that chrysotoxene (phenanthrene derivative that was first isolated from Dendrobium chrysotoxum) (20 mg/kg) indicated that it significantly (p < 0.01) the inhibited growth of HepG2 cell-induced tumors by regulating the aforementioned apoptotic proteins (Smac, Cytochrome c, Survivin, Bcl-2, Bax, Apaf-1, c-caspase-9, and c-caspase-3), compared with the control group.…”
Section: In Vivo Studies Of Extracts and Pure Compounds From The Orch...mentioning
confidence: 60%
“…The authors revealed that on the tenth day after tumor cell inoculation, the mouse abdominal perimeter and weight in the PRP treatment group were significantly smaller than those in the control group. Collectively, these results demonstrated that PRP has significant antitumour properties in the H22 tumor model [218]. Other studies in xenograft analysis showed that chrysotoxene (phenanthrene derivative that was first isolated from Dendrobium chrysotoxum) (20 mg/kg) indicated that it significantly (p < 0.01) the inhibited growth of HepG2 cell-induced tumors by regulating the aforementioned apoptotic proteins (Smac, Cytochrome c, Survivin, Bcl-2, Bax, Apaf-1, c-caspase-9, and c-caspase-3), compared with the control group.…”
Section: In Vivo Studies Of Extracts and Pure Compounds From The Orch...mentioning
confidence: 60%
“…2 that reflects the anti-ascites attributes of our extracted polysaccharide. Re-occurrence of tumor cells is one of the crucial hurdles in achieving successful cancer therapy (Fang et al 2018 ). Foxp3 and Stat3 genes were observed down-regulated in polysaccharide treated groups as compared to their control group that shows no signs of disease re-occurrence results presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The lung cancer cell strain was examined as described previously ( Fang et al, 2018 ). Four types of human LC cell lines were measured by CCK-8 (Dojindo, Japan), as per the instruction.…”
Section: Methodsmentioning
confidence: 99%
“…Before the STAT3 expression level of two groups was detected by western blot, puromycin (puro) at the concentration of 2.5 μg/ ml was added for the selection of stable cell lines. The cell viabilities of stable strains were measured by CCK-8 (Dojindo, Japan) in the above method ( Fang et al, 2018 ), where the mediums were mixed with AETW at 0.5 mg/ml and only cultured for 48 h.…”
Section: Methodsmentioning
confidence: 99%